Effect of Fungicides and Plant Extracts in the Management of Foliar, Twig and Fruit Diseases of Citrus (Citrus limon)
A research work was conducted on citrus plants raised at GPC, of Fruit Tree Improvement Project (FTIP) at Horticulture Farm, Bangladesh Agricultural University, Mymensingh, to investigate the effect of fungicides and plant extracts in controlling the scab, die-back and canker. Three fungicides viz. Cupravit 50 wp (0.4%), Dithane M-45 (0.3%), Rovral 50 WP (0.2%) and extracts of 3 plants viz. Neem Azadirachta indica), Ginger Zingiber officinale) and Garlic Allium sativum) were applied for controlling the citrus (C. limon) diseases (scab, die-back and canker). All the fungicides showed significant effect in the control of the above mentioned citrus diseases. The highest reduction of the scab, die-back and canker diseases was recorded applying Rovral 50 WP. Neem leaf extract was the most effective in controlling canker of leaf and fruit. Garlic extract and Neem leaf extract were the most effective in controlling die-back of twig and branches of citrus, respectively. From the above results it can be concluded that Rovral 50 WP is the most effective chemical for controlling all citrus (C. limon) diseases and citrus canker can successfully be controlled specially by Neem leaf and garlic extract. J. Environ. Sci. & Natural Resources, 10(1): 93-100 2017 , number=1, journal=Journal of Environmental Science and Natural Resources, author=Yesmin, K and Ahmad, M and Momtaz, MB and Begum, K, year=2017, month=Nov., pages=93–100